New Insights on Hepatic De Novo Lipogenesis in Rat's Fetus. (7th June 2021) - Manca, Claudia; Murru, Elisabetta; Carta, Gianfranca; Santoni, Michele; Pistis, Marco; Banni, Sebastiano
Abstract: Objectives: Among the macronutrients provided by the mothers to fetuses free fatty acids (FFA), particularly palmitic acid and glycerol cross the placental barrier in smaller proportions respect to glucose and amino acids, due to a minor placental permeability. It has already been suggested that during advanced gestation, fetal FA are mainly derived from de novo lipogenesis (DNL) in the fetal liver. Therefore, the aim of this study was to evaluate DNL metabolic biomarkers in fetuses of rat dams at gestational day (GD) 16, which represent the beginning of the third stage of gestation. Peculiarly, besides the usual lipid biomarkers of DNL, increase of PA and POA and the ratio PA/LA, we also evaluated whether C16:0 ceramide biosynthesis was enhanced by DNL thereby representing a novel biomarker of DNL. Methods: The profile of FA and ceramides was measured by using LC-DAD and MS/MS in line in liver of rat dams sacrificed at GD16 and their fetuses. Differences between rat dams and their fetuses were determined by an Mann-Whitney unpaired test. Results: Our results show that lipid metabolism in the liver of fetuses, when compared to those of their mother, was characterized by profound differences in the fatty acid profile, i.e., increased levels of the palmitic acid (16:0) (1.24 fold; p = 0.04) and its desaturase product palmitoleic acid (16:1-n7) (2.5 fold; p = 0.002) indicating an overactive DNL. Peculiarly, we found striking higher levels (30 fold; p = 0.02) in fetal liver respect to rat dams liver of C16:0 ceramide, while the other ceramides species didn't increase significantly. Conclusions: Our data suggest that the 16:0 to form fetal C16:0 ceramide derives from DNL. C16:0 ceramide in adults is usually associated to impaired insulin signalling and energy homeostasis, and eventually to insulin resistance and type 2 diabetes. On the other hand, it has also been shown that C16:0 ceramide sustains lipogenesis, which may be functional to the increased fetal growth rate characteristic of the last gestational stage. Funding Sources: This study was supported by grant from the Ministry of University and Research (MUR) - Proof of Concept 2018.